2016
DOI: 10.21767/2471-853x.100036
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine Use and Liver Disease are Associated with All-Cause Mortality in the Miami Adult Studies in HIV (MASH) Cohort

Abstract: Objective Liver disease is a frequent cause of morbidity and mortality in HIV infection. We examined the relationship of cocaine use, liver disease progression and mortality in an HIV-infected cohort. Methods Consent was obtained from 487 HIV+ participants, a subset of the Miami Adult Studies on HIV (MASH) cohort. Participants were eligible if they were followed for at least two years, completed questionnaires on demographics and illicit drug use and had complete metabolic panels, CD4 cell counts and HIV-vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…In the present study, both baseline FIB-4 higher than 3.25, indicating advanced liver fibrosis, and FIB-4 progressing from mild to advanced fibrosis during follow-up were found to be independent predictors for all-cause mortality among HIV/HCV co-infected participants under cART. This observation is consistent with studies conducted in the western countries (31)(32)(33). One large scale cohort conducted in Italy followed up 3,475 HIV patients with or without HCV reported that FIB-4 at cART initiation and its change independently predicted liver related death (34).…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, both baseline FIB-4 higher than 3.25, indicating advanced liver fibrosis, and FIB-4 progressing from mild to advanced fibrosis during follow-up were found to be independent predictors for all-cause mortality among HIV/HCV co-infected participants under cART. This observation is consistent with studies conducted in the western countries (31)(32)(33). One large scale cohort conducted in Italy followed up 3,475 HIV patients with or without HCV reported that FIB-4 at cART initiation and its change independently predicted liver related death (34).…”
Section: Discussionsupporting
confidence: 89%
“…Further details related to the methodology of the original project can be found in a paper entitled, ‘Cocaine Use and Liver Disease are Associated with All-Cause Mortality in the Miami Adult Studies in HIV (MASH) Cohort’. 15 This is a secondary analysis of a prospective cohort study involving 407 individuals living with HIV and residing in the south Florida region. Participants were a subset of the more than 800 participants from the MASH cohort who have been followed from 2009 to 2014.…”
Section: Methodsmentioning
confidence: 99%
“…In Miami-Dade County, where the use of cocaine is frequent among PLWH and the incidence of HIV is the highest in the United States [4], cocaine use has been associated with increased mortality in the Miami Adult Studies on HIV (MASH) cohort [5]. Cocaine use was associated with, HIV-related mortality and cardio-pulmonary deaths, the two main causes of death in this report [5].…”
mentioning
confidence: 74%
“…The results from the MASH cohort suggest that cocaine use may precipitate death in this population through behavioral and biological effects [5][6][7][8][9][10]. Behavioral factors such as engaging in illegal and addictive drug use will lessen the possibility of early HIV testing, and reduce the potential for accessing and adhering to antiretroviral treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation